2017
DOI: 10.5455/javar.2017.d187
|View full text |Cite
|
Sign up to set email alerts
|

Clinical management of maggot wounds in Bengal Tigers (Panthera tigris tigris)

Abstract: Objecitve: Maggot wound is common in domestic and pet animals but report on maggot wound treatment in wildlife species is scanty. The study reported here the surgical and conservative management of maggot wounds including anesthetic protocol and postoperative care in two Bengal tigers (Panthera tigris tigris). Materials and methods: One female and one male tiger were presented with maggot wounds for treatment at the Bangabandhu Sheikh Mujib Safari Park, Gazipur, Bangladesh. Tigers were anesthetized with combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…The above-mentioned method is economical for the treatment of a large number of animals at zoos or safari. In this report, maggot wounds healed completely on 10 th day of infection while surgical operation healed the wound on 12 th day after operation in tigers (Talukder et al, 2017). Rehamn et al (2009) reported maggot wound healing at day 17 after treatment in cattle treated with broad spectrum antibiotics.…”
Section: Treatment and Discussionmentioning
confidence: 58%
“…The above-mentioned method is economical for the treatment of a large number of animals at zoos or safari. In this report, maggot wounds healed completely on 10 th day of infection while surgical operation healed the wound on 12 th day after operation in tigers (Talukder et al, 2017). Rehamn et al (2009) reported maggot wound healing at day 17 after treatment in cattle treated with broad spectrum antibiotics.…”
Section: Treatment and Discussionmentioning
confidence: 58%